PEMBUATAN HYDROFOIL TURBIN DARRIEUS - M, Muharnif; Nasution, Elvy Sahnur (Universitas Malikussaleh, 2018)
Hydrokinetic water turbines do not require high water pressure (head) to work.Another advantage of the Darrieus turbine is that it is less sensitive to turbulencebut sensitive to flow direction. Among some forms of turbine turbine turbinegeometry, straight-angled geometry (or H-Darrieus) is more popular due to easierfabrication and simpler construction. The number of blades using the NACA type0012 H-rotor has the best self-starting effect but not for all azimuth blade positions.If the blade is fixed and unregulated then the angle of charge will change at anytime depending on the position of the blade which consequently alters thedynamic force of the water to the blade and therefore tends to occur in the lowtorque of the tubin and decrease the turbine effiency. One disadvantage of theDarrieus turbine is its low self-starting torque. So the problem in this research ishow the turbine produced performance with variation of the number of blades.The study was conducted to analyze the perforamance of low-speed darrieusturbines shown by self-starting characteristics, dynamic torque, power, andefficiency produced by turbines. The test rig comprises two main components: amodel of stream flow made of acrylic and a model of the Darrieus turbine. Rivermodels from upstream shelters, canals and downstream water reservoirs. Waterfrom upstream flows into the runner through the incoming side. Then waterflowed into the downstream storage basin. In the construction of this model is notmunggunakan draft tube. The runner house has a fully enclosed top casing with nodraft tube and wall, the water flow rate and Head of water level are set by the feedwater pump. The difference between the water level in the upstream reservoir andthe water level in the canal is kept constant. Once the above is achieved then it canbe tested. The shaft rotation is measured by the rotation sensor and the shafttorque force is measured using a load cell. Experiments carried out with variationsof torque loads with constant flow rate of water The manufacture of the Darrieousturbine model testing apparatus has been completed. This model comes with aData acquisition Tool using arduino UNO with DAQ PLX that works according toplan. In taking the research dataKey word: Darrieus turbine, hydrofoil,manufacture